Shifting the Status Quo: Constitutional Reforms in Chile. (2nd January 2018) - Fuentes, Claudio
Abstract: This article outlines the factors that explain changes in the rules of the game in Chile after the restoration of democracy in 1990. It looks particularly at the reasons why the right-wing parties—strong defenders of the constitution imposed by General Augusto Pinochet in 1980—accepted reforms that eliminated many of what the literature has termed authoritarian enclaves. The article explains this shift by observing significant changes in the political context that, in turn, affected the priorities of veto players. In this context, short-term strategic calculations by the right-wing parties, aiming to achieve a new balance of power less detrimental to their interests, opened a window of opportunity that led to congressional approval of important reforms. Particular institutional features of the Chilean political system—party discipline and a balance of power in favor of the executive—also helped the political actors to reach agreement.